Molecular and spatial evaluation of small rodents and Didelphimorphis infected with Mycobacterium leprae in the southern Amazon, Brazil - Valois, Élderson Mariano de Souza; Oliveira, Nathan Guilherme De; de Lázari, Patrick Ricardo; da Silva, David José Ferreira; Rotelli, Raissa Campos; Batista, Lavinia Cassia Ferreira; Sobral, Marcos Henrique; Bortolomai, Bruna Eduarda; Ribeiro, Amanda Finardi; Levi, Taal; Peres, Carlos Augusto; de Morais Bronzoni, Roberta Vieira; et al. (Wiley, 2024)
BACKGROUND: The high levels of recent transmission of leprosy worldwide demonstrate the necessity of epidemiologic surveillance to understand and control its dissemination. Brazil remains the second in number of cases around the world, indicating active transmission of Mycobacterium leprae (M. leprae) in the population. At this moment, there is a consensus that the bacillus is transmitted by inter-human contact, however, different serologic, molecular, and histopathological approaches indicate the existence of non-human transmission sources. METHODS AND RESULTS: The qPCR assay was used to amplify the molecular targets 16S RNAr and RLEP, in samples of liver, spleen, and ear of wild animals belonging to Didelphimorphia and Rodentia orders, in highly endemic areas of Mato Grosso, Brazil. The RLEP repetitive sequence was positive in 202 (89.0%) samples, with 96 (42.3%) of these also being positive for the 16S gene. Regarding the collection sites, it was observed that the animals were found in areas profoundly deforested, close to urban areas. CONCLUSIONS: Our results suggest that wild animals can play an important role in the maintenance of M. leprae in endemic regions with major anthropic action in Brazil. Therefore, integrating human, animal, and environmental health care with the One Health initiative is highly efficient for the development of effective strategies to contain and control leprosy in Brazil.